SMART-INFRASTRUCTURE IN THE SUSTAINABLE DEVELOPMENT OF THE CITY: WORLD EXPERIENCE AND PROSPECTS OF UKRAINE - But , Tetiana; Mamotenko , Daria; Hres-Yevreinova , Svitlana (Collection of scientific papers «ΛΌГOΣ», 2023)
Smart infrastructure is one of the main components of the digital economy, which consists of many different structures. Such infrastructure is the basis for many new services, applications and business models. Today, individual cities are gradually turning into «intelligent systems», where digital technologies are spreading to an increasing number of areas – healthcare, education, energy, security, transport, resource management. It is thanks to the use of digital technologies aimed at improving the overall well-being of residents that traditional networks and services become more efficient in a smart city. At the end of 2020, the «Digital Europe» Program for 2021-2027 was approved, which provides for the large-scale implementation of digital solutions for cities and communities.